2019
DOI: 10.1007/978-981-13-8871-2_33
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic Roles of RAAS Blockers: Update

Abstract: The rennin-angiotensin-aldosterone system (RAAS) has been well documented in regulating blood pressure, fluid volume, and sodium balance. Overactivity of RAAS promotes both systemic and regional glomerular capillary hypertension, which could induce hemodynamic injury to the glomerulus, leading to kidney damage and renal fibrosis via profibrotic and proinflammatory pathway. Therefore, the use of RAAS inhibitors (i.e., ACEIs, ARBs, and MRAs) as the optional therapy has been demonstrated to prevent proteinuria, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 90 publications
(91 reference statements)
0
16
0
Order By: Relevance
“…The rennin‐angiotensin‐aldosterone system (RAAS) has been well documented and reported for the regulation of blood pressure, fluid volume, and sodium balance (Zhang et al, 2019). Therefore, over activity of RAAS has been reported to promote both systemic and regional glomerular capillary hypertension leading to renal damage, vasoconstriction, endothelial dysfunction, thrombosis, inflammation, and fibrosis via proinflammatory pathways (Gromotowicz‐Poplawska et al, 2016; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rennin‐angiotensin‐aldosterone system (RAAS) has been well documented and reported for the regulation of blood pressure, fluid volume, and sodium balance (Zhang et al, 2019). Therefore, over activity of RAAS has been reported to promote both systemic and regional glomerular capillary hypertension leading to renal damage, vasoconstriction, endothelial dysfunction, thrombosis, inflammation, and fibrosis via proinflammatory pathways (Gromotowicz‐Poplawska et al, 2016; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The rennin‐angiotensin‐aldosterone system (RAAS) has been well documented and reported for the regulation of blood pressure, fluid volume, and sodium balance (Zhang et al, 2019). Therefore, over activity of RAAS has been reported to promote both systemic and regional glomerular capillary hypertension leading to renal damage, vasoconstriction, endothelial dysfunction, thrombosis, inflammation, and fibrosis via proinflammatory pathways (Gromotowicz‐Poplawska et al, 2016; Zhang et al, 2019). Angiotensin‐converting enzyme (ACE) inhibitors prevent the formation of more physiologically active angiotensin II from its precursor angiotensin I, and are, therefore, effective for the management of hypertension due to excessive generalized vasoconstriction in the cardiovascular system (Bhandari & Chadburn, 2019; Podzolkov & Tarzimanova, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Non-specific therapies for CKD can slow and even halt progressive loss of kidney function. These include diet and medications for blood pressure control (target <130/80) ( Faqah and Jafar, 2011 ), antifibrotic therapies (inhibitors of renin, angiotensin II, and aldosterone, the latter being a potent profibrotic molecule) ( Zhang et al, 2019 ), and dietary sodium restriction and thiazide diuretics (the latter potentiates the antiproteinuric effects of the renin-angiotensin-aldosterone system antagonists) ( Park et al, 2014 ). SGLT2 inhibitors reduce progression of kidney damage in diabetes ( Tuttle et al, 2021 ) and recently this effect has been shown in non-diabetic kidney disease as well, possibly by reducing proximal tubule stress ( Almaimani et al, 2021 ).…”
Section: Ckd Therapiesmentioning
confidence: 99%
“…ACE-2 cleaves Ang II to Ang (1–7) and exerts vasodilatation, anti-inflammation, and anti-fibrotic effects by Mas receptor system activation. RAAS activation effects depend on the tissue ACE/ACE2 balance, which could be affected by several factors [ 44 , 45 , 46 ].…”
Section: Pathophysiological Mechanisms Of Sars-cov-2 and Its Neurological Implicationsmentioning
confidence: 99%